Strategic Road Maintenance and Development Programme of the Republic of Lithuania for 2030 – a Tool for Using National Funds to Create a Sustainable and Viable Road Network - Evaldas Morkūnas (The Baltic Journal of Road and Bridge Engineering, 2015)
Road are significant national assets which provides a fundamental foundation to the performance of all national economies, delivering conditions for social and economic development of countries and international communities. It is of at most importance to ensure a mobile and safe movement of inhabitants with the lowest time and pollution costs. In order to reach the goals the planning processes are implemented on a national and international scale to rationally justify the efficiency of urgent measures. In the Republic of Lithuania, seeking to efficiently use funds allocated to the road sector the Road Maintenance and Development Programmes are developed by the road manager defining a short-term and long-term vision of the road network and measures to achieve it. However, due to the anticipated insufficient financing of the road sector the Road Maintenance and Development Programmes aim to rationally combine preservation of the road network and its perspective development depending on the existing financing. The Road Maintenance and Development Programme of the Republic of Lithuania for 2030 assesses the existing condition of the road network and defines the goals and measures how to implement a sustainable development in the road network. With the help of review analysis this paper studies: road safety assurance, road pavement deterioration degree, social welfare assurance, road maintenance, infrastructure development, assurance of sustainable development.